Diseño de red multisede simulada con transición a ipv6 mediante esquema dual stack - Yaguana López, Cristhian Alberto (Machala : Universidad Técnica de Machala, 2025)
This case study addresses the need of CONRAP, a technology consulting firm with offices in Cuenca, Azogues and Machala, to modernize and unify its network infrastructure in view of the progressive migration to IPv6, without losing compatibility with current services. The objective is to implement a scalable, secure and functional dual-stack network that allows the efficient interconnection of its offices and integrates internal services such as HTTP and DNS for continuous access to essential and shared resources. The technical proposal contemplates a logical network design that supports IPv4 and IPv6 simultaneously, using dynamic routing with OSPFv2 (IPv4) and OSPFv3 (IPv6) to guarantee redundancy, efficiency and operational continuity. VLAN segmentation will also be used to optimize internal traffic and reinforce interdepartmental security, ensuring more efficient management of available technological resources. Each site will have a router, a layer 3 switch and HTTP/DNS servers, while in Cuenca a DHCPv6 server will be implemented to allow automatic assignment of network parameters in IPv6 environments. The validation will be done through detailed simulations in Cisco Packet Tracer, configuring dual-stack interfaces, subinterfaces, VLANs, routing and essential network services. The aim is to verify connectivity between offices and departments, the operation of services in both protocols, name resolution through DNS and automatic address assignment with DHCPv6. This project represents a model applicable to companies seeking to adopt IPv6 in a gradual, orderly and effective manner, without compromising the operability of their corporate network.
Este caso de estudio aborda la necesidad de CONRAP, consultora tecnológica con sedes en Cuenca, Azogues y Machala, de modernizar y unificar su infraestructura de red ante la migración progresiva hacia IPv6, sin perder compatibilidad con los servicios actuales. El objetivo es implementar una red dual-stack escalable, segura y funcional, que permita la interconexión eficiente de sus sedes e integre servicios internos como HTTP y DNS para el acceso continuo a recursos esenciales y compartidos. La propuesta técnica contempla un diseño lógico de red que soporte IPv4 e IPv6 simultáneamente, empleando enrutamiento dinámico con OSPFv2 (IPv4) y OSPFv3 (IPv6) para garantizar redundancia, eficiencia y continuidad operativa. También se utilizará segmentación por VLANs para optimizar el tráfico interno y reforzar la seguridad entre departamentos, asegurando una administración más eficiente de los recursos tecnológicos disponibles. Cada sede dispondrá de un router, un switch de capa 3 y servidores HTTP/DNS, mientras que en Cuenca se implementará un servidor DHCPv6 que permita la asignación automática de parámetros de red en entornos IPv6. La validación se realizará mediante simulaciones detalladas en Cisco Packet Tracer, configurando interfaces dual-stack, subinterfaces, VLANs, enrutamiento y servicios esenciales de red. Se busca verificar la conectividad entre sedes y departamentos, el funcionamiento de los servicios en ambos protocolos, la resolución de nombres a través del DNS y la asignación automática de direcciones con DHCPv6. Este proyecto representa un modelo aplicable a empresas que buscan adoptar IPv6 de forma gradual, ordenada, efectiva y sin comprometer la operatividad de su red corporativa.
Keywords: IPV6; DUAL-STACK; MULTI-SEDE; PROTOCOLOS